Quantification of nanoscale forces in lectin-mediated bacterial attachment and uptake into giant liposomes. Issue 7 (27th January 2021) - Omidvar, Ramin; Ayala, Yareni A.; Brandel, Annette; Hasenclever, Lukas; Helmstädter, Martin; Rohrbach, Alexander; Römer, Winfried; Madl, Josef
Abstract : Two force probing methods were used to quantify nanoscale forces in the interaction of the bacterial lectin LecA with the glycolipid Gb3, revealing how the interaction aids bacterial attachment and lowers the energy required for bacterial uptake. Abstract : Interactions of the bacterial lectin LecA with the host cells glycosphingolipid Gb3 have been shown to be crucial for the cellular uptake of the bacterium Pseudomonas aeruginosa . LecA-induced Gb3 clustering, referred to as lipid zipper mechanism, leads to full membrane engulfment of the bacterium. Here, we aim for a nanoscale force characterization of this mechanism using two complementary force probing techniques, atomic force microscopy (AFM) and optical tweezers (OT). The LecA–Gb3 interactions are reconstituted using giant unilamellar vesicles (GUVs), a well-controlled minimal system mimicking the plasma membrane and nanoscale forces between either bacteria (PAO1 wild-type and LecA-deletion mutant strains) or LecA-coated probes (as minimal, synthetic bacterial model) and vesicles are measured. LecA–Gb3 interactions strengthen the bacterial attachment to the membrane (1.5–8-fold) depending on the membrane tension and the applied technique. Moreover, significantly less energy (reduction up to 80%) is required for the full uptake of LecA-coated beads into Gb3-functionalized vesicles. This quantitative approach highlights that lectin–glycolipid interactions provide adequate forces and energies to drive bacterial attachment and uptake.